Prognostic impact of margin status in liver resections for colorectal metastases after bevacizumab - Sasaki, Kazunari; Polychronidis, Georgios (The British journal of surgery, 2017)
Background: Margin status with resection of colorectal liver metastasis (CRLM) was an important prognostic factor in the years before the introduction of biological chemotherapy. This study examined outcomes following CRLM resection in patients who received neoadjuvant chemotherapy with or without the monoclonal antiangiogenic antibody bevacizumab. Methods: Patients who underwent surgery for CRLM at the Johns Hopkins Hospital between 2000 and 2015 were identified from an institutional database. Data regarding surgical margin status, preoperative bevacizumab administration and overall survival (OS) were assessed using multivariable analyses. Results: Of 630 patients who underwent CRLM resection, 417 (66⋅2 per cent) received neoadjuvant chemotherapy with (214, 34⋅0 per cent) or without (203, 32⋅2 per cent) bevacizumab. The remaining 213 (33⋅8 per cent) did not receive neoadjuvant chemotherapy. Univariable analysis found that positive margins were associated with worse 5-year OS than R0 resection (36⋅2 versus 54⋅9 per cent; P = 0⋅005). After dichotomizing by the receipt of preopera tive bevacizumab versus chemotherapy alone, the prognostic value of pathological margin persisted among patients who did not receive preoperative bevacizumab (5-year OS 53⋅0 versus 37 per cent after R0 versus R1 resection; P = 0⋅010). OS was not signifocantly associated with margin status in bevacizumab-treated patients (5-year OS 46⋅8 versus 33 per cent after R0 versus R1 resection; P = 0⋅081), in whom 5-year survival was slightly worse (presumably reflecting more advanced disease) than among patients treated with cytotoxic agents alone. Pathological margin status was not significantly associated with 5-year OS in patients with a complete or near-complete response to chemotherapy and bevacizumab (43 versus 30 per cent after R0 versus R1 resection; P = 0⋅917), but this may be due to a type II error. Conclusion: The impact of margin status varied according to the receipt of bevacizumab. Bevacizumab may have a role to play in improving outcomes among patients with more advanced disease.